Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-5470-145

+91 7353221155

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

how can we find out f(x)?? if something like f(x+y)=f(x)+f(y) is given and it also say f(1)=2 so now also find f(2)..??  for functional equations watz the procedure to find out f(x)??

12 years ago

Hi,

It is given that f(x+y) =f(x)+f(y)  and f(1)=2

so on keeping x=1 and y=0 in the above eqn we  get

f(1)=f(1) +f(0)  =>  f(0)=0  now when we keep x=1 and y=1 we get

f(2)=f(1)+f(1)  =>f(2)=4

similarly when we calculate f(3) and f(4) we get them as 6 and 8 respectively.On observing the sequence we come to know that

f(x)=2x

12 years ago

put x=y

then f(2x)=2f(x)

so f(0) = 0

given f(1) = 2

so for x=y=1 f(2) = 2f(1) = 4

so f(2) =4

for x= -y

f(x) + f(-x) = 0

so f(-x) = -f(x)  so f(x) is odd function

if we take f(x) to be a polynomia function then

f(x) is of form (px)2n+1

for p=2 and n=0 , we have f(x) = 2x    which fits in f(0) , f(1) and f(2) .

SO f(x) = 2x